HUBUNGAN ANTARAKESADARAN METAKOGNITIFDENGAN HASIL BELAJAR MEKANIKA TEKNIK MAHASISWA JURUSAN TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - 2017-2021, Afriza Wati (Universitas Negeri Padang, 2018)
Abstract— This research was conducted because the percentage of students of Building Engineering Education Study Program that do not pass in Mechanical Engineering is quite high. The purpose is to reveal the relationship between metacognitive awareness with the learning result of Student Engineering Mechanics of PTB Program of Civil Engineering Department of FT UNP2015 and 2016. This research is correlational research with quantitative approach, with sample of 62 respondents. This Research using Instrument Metacognitive Awareness Inventory (MAI) adapted from Schraw and Dennison (1994). Measurement scale using guttman scale with 2 choices of answers, yes or no. The data were analyzed using SPSS 17.00 program and it was found that the metacgnitive awareness and learning achievement was strongly correlated with rhitung 0,502 and rtabel was 0,250. Level of correlation and the strength of the relationship between the two variables is strong enough meaning, the two variables have a reciprocal relationship, if students metacogntif awareness high, then student learning outcomes will be high. Conversely, if metacognitive awareness is low, then learning outcomes will be low as well. Keywords: Metacognitive Awareness, Learning Outcomes